THE IMPACT OF THE DIGITAL ERA ON TRADITIONAL EDUCATION - Ochilova Gulshoda Asatillo qizi (Ustozlar uchun, 2025)
Abstract: This article explores the transformation of traditional education systems brought about by the digital era. The introduction of digital technology has revolutionized educational paradigms by implementing innovative teaching methods, enhancing accessibility, and creating interactive learning environments. Through a thorough analysis of recent studies and empirical data, this article investigates the objectives and methods of the digital revolution in education. Key findings reveal benefits such as heightened student engagement and personalized learning, along with challenges like the digital divide and the need for updated teacher training. The conclusion underscores the necessity for a balanced integration of digital tools within traditional education to maximize their advantages while minimizing drawbacks. By assessing the current landscape and forecasting future trends, this article offers insights for educators, policymakers, and stakeholders aiming to effectively navigate the digital shift.